Pengaruh Bauran Promosi dan Harga Terhadap Keputusan Pembelian Pada Produk Elektronik (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2022)
With the decline in consumer purchasing decisions accompanied by pandemic conditions and current visiting restrictions, the main thing that the company needs to prioritize is customer satisfaction in order to survive and compete in market share. Management must know what things are considered important in order to attract consumer buying interest in electronic products, so that leaders are required to always produce performance, especially in the promotion mix and prices so that they are considered to be able to attract consumers to visit and decide to buy electronic products. The purpose of this study was to determine the effect of simultaneous, partial and dominant promotion mix and price on purchasing decisions on electronic products at Giant Ekstra Waru Sidoarjo. The type of data used is quantitative data and according to data sources, primary and secondary data are used. The number of research samples was determined using the purposive sampling method as many as 74 respondents. The data were collected using a questionnaire method whose measurements used a Likert scale and analyzed statistically using multiple linear regression analysis, coefficient of determination, F-test and T-test using SPSS version 21. Based on the results of data analysis, the results showed that there was a positive and negative effect Simultaneously and partially significant between the promotion mix and price on purchasing decisions on electronic products at Giant Ekstra Waru Sidoarjo. Based on the dominant test results show that the promotion mix has a dominant influence on purchasing decisions on electronic products. The management should pay attention to and improve the company's promotional mix for purchasing decisions to maintain customer satisfaction by opening a shopping service from home and providing the best price that is proportional to the benefits obtained by consumers.